ANALISIS KESULITAN SISWA DALAM MENGERJAKANSOAL CERITA MATEMATIKA MATERI ARITMATIKA SOSIAL DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SMP NEGERI 5 METRO TAHUN PELAJARAN 2015/2016 - Amalia Zulvia Widyaningrum (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
This research aims to review the mistake of students in resolving word problems, in terms of the study and described factors. Subjects research is Grade VII students of SMPN 5 Metro. The research is descriptive qualitative. The collection includes the survey data student’s learning style, the test sheets, and intervie. The results of the research is visual students dominant made an interpretation language mistake, auditorial students dominant made a technical mistake, and kinesthetic students dominant made an interpretation language and technical mistake. The Factors affecting students made a mistake in resolving word problems math is: a) Misinterpret about the formula that used to make a mathematics sentence. b) did not understand model or mathematics sentence. c) mastery the concept of a prerequisite immature. d) less well in understanding and read handling of about. e) reasoning a less well to translate intent and direction about. f) impression negative on word problems seen scary and make students lazy to read about. g) not scrupulous or meticulously in reading and tend to careless in the surgery on about. h) could not distinguish between answers model or sentence mathematics with the final answer questions. Keywords: student’s error, mathematics word problems, learning styles